Developing insights on branding in the B2B context : case studies from business practice - Koporcic, Nikolina; Ivanova-Gongne, Maria, 1985-; Nyström, Anna-Greta, 1979-; Törnroos, Jan-Åke (Emerald Publishing Limited, 2018)
This book presents real life business-to-business (B2B) branding cases. The book deploys a theoretical-practical approach, where theoretical and conceptual frameworks related to key branding topics are supported by empirical case studies. Each case helps to illustrate the framework and discuss its applicability in practice. Through the presented exploratory case studies, the authors provide fresh examples from business practice that are easy to comprehend by undergraduate students, and are easily applied by managers in the field. The book consists of three main parts, covering important aspects of B2B branding. It presents several aspects of external as well as internal branding, supplemented by novel approaches in B2B branding. In addition, the book offers examples of best practices, as well as notable mistakes made by companies involved in branding processes. Thus, it provides a holistic perspective, which will enable companies to learn not only about best practices, but also about pitfalls in the area of corporate branding. In addition to the novel practical cases, each chapter provides relevant theoretical underpinnings presented in a simple, down-to-earth manner. The book highlights recent research areas and coming trends within B2B branding. The book is suitable for everyone with an interest in B2B branding, regardless of background or previous knowledge of branding.